Effect of Varying Levels of Moringa oleifera Leaf meal on In-vitro Utilization, Digestibility, Intake, Milk Production, Milk composition and Fatty Acid Profile of Milk in Lactating Goats - Gursimran Singh; J.S. Lamba; R.S. Grewal; Jasmine Kaur; Shashi Nayyar; Mandeep Singla (Indian Journal of Animal Nutrition, 2022)
The effects of substituting crude protein (CP) in soybean meal with Moringa oleifera leaf meal (MLM) supplementation on milk production parameters and nutrient utilization in lactating goats were examined in current study. To determine the best level of MLM for the in vivo trial, an in vitro experiment was undertaken with MLM inclusion rates of 0,10, 20, 30, 40 and 50% of the CP of soyabean meal replaced. Net gas production, total volatile fatty acid and propionic acid concentrations were significantly higher in 30% MLM total mixed ration (TMR). Twelve lactating goats were randomly assigned to control group and MLM group in the in vivo trial, with six animals in each group. According to in vitro results, the experimental diets used in in vivo study were, a control (soybean meal as a main protein source) and MLM (CP of soybean was replaced by 30% MLM) diet. Lactating goats were fed a 60:40 TMR of fodder and concentrate respectively. Feeding of MLM resulted in significantly higher digestibility of ADF, Cellulose, OM and NFC. The DM intake and nutrients (CP, EE, NDF and ADF) intake (% BW) were found to be similar. Supplementation of MLM had no significant (P<0.05) effect on average milk yield, milk composition (protein, SNF, lactose and fat) and ECM. Fatty acid (FA) profiles of milk revealed that the levels of saturated, monounsaturated and polyunsaturated FA were similar in both the groups. Hence, it can be concluded that MLM can replace 30% CP of soyabean meal in the ration of lactating goats.